PERENCANAAN PEMBANGUNAN WILAYAH BERDASARKAN KONSEP PRODUKTIFITAS UNGGULAN - Mawardi, Ikhwanuddin (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
Productivity is a ratio between an output and another input, such as: labor,and land. To solve the problem of resource limitation, it is necessary todevelop some approaches, such as priority commodity approach and priorityterritory development approach. Some factors influencing the problem ofnon optimal development are very low development of Iceal prioritycommodity and undevelopment of priority area. Several policies andstrategies that are needed in order to increase an area productivity is through priority sector / commodity development which is adjusted with carrying capacity of adjacent area, labor mobilization and human resourcedevelopment. In order to support the direction of those policy and strategy,some programs that are developed are: reorientation program of localeconomic development that based on priority commodity, developmentprogram of strategic area and human resources development, quantitycallyand qualitycally. In order to get a huge output to increase the people welfare, it is necessary to choose a right local priority commodity, thus others priority sectors will also be developed.